Target genes involved in corticosterone-induced PC12 cell viability and neurite disorders: A potential molecular mechanism of major depressive disorder. (30th January 2016) - Li, Mingzhen; Zhou, Jianjun; Qian, Jialin; Cheng, Xiaoyan; Wu, Huijuan; Li, Li; Qian, Chunyan; Su, Joyce; Wu, Donald; Burns, Larry; Golden, Teresa; Wu, Ning
Abstract: Past studies confirmed that hypothalamic-pituitary-adrenal (HPA)-axis hormones involved in major depressive disorder (MDD) development. This study used corticosterone treated PC12 cells to explore the potential role of MAPK signal transduction pathway in response to corticosterone stimulation. The results showed that both live cell numbers and cellular neurite outgrowth were remarkably reduced in response to corticosterone treatments. qPCR results demonstrated that the expression levels of four MAPK pathway genes were significantly increased after corticosterone stimulation. In conclusion, glucocorticoids stimulation can affect neuronal cell viability and neurite outgrowth due to the over expression of a group of MAPK pathway genes. Highlights: Illustrating corticosterone-induced PC12 cell viability and neurite changes. Identifying genes involved in corticosterone-induced PC12 cell changes. Analyzing the potential interactive mechanisms among the target genes.